Somme approaches to measure corporate profitability in relation to customer loyalty and employee satisfaction. “The case of Arica” - Viera Castillo, Daniel (2015)
The purpose is to identify whether employee satisfaction is directly related to customer loyalty, and therefore in corporate profitability. Three direct relationships were analyzed: (1) the direct relationship between employee satisfaction and customer loyalty, (2) the direct relationship between customer loyalty and profitability, and (3) the direct relationship between employee satisfaction and business profitability. The data required for this study were collected from employees and customers of banks, in addition to the balances of each of these. A structural equation model was used to test the hypotheses. Preliminary results of this model indicated that the initial model should be reconsidered, and therefore limit the model was due omitting any relationship with corporate profitability as a result of the low number of banks and the high number of customers in the sample used prevent statistical adjustments.Keywords: financial performance, employee satisfaction, customer loyalty, customer satisfaction, image, commitment, trust.